Can senior executive characteristics improve carbon emission performance? Evidence from China - Liu, Xun; He, Mengqi; Zhang, Shaoyong; Zhuang, Zhao; Cai, Cheng (Frontiers in Ecology and Evolution, 2023)
In recent years, the backbone of China's market economy has involved controlling corporate carbon emissions and reducing environmental pollution. This study aimed to investigate the relationship between the characteristics of senior managers and the carbon emission performance of enterprises. The empirical study used panel data on high-emission industries operating in the China A-shares market from 2014 to 2017. The results showed that the natural age, education level, and professional background of senior managers in high-emission enterprises were negatively correlated with the carbon emission performance of enterprises. However, in the case of large enterprises, there is no strong relationship between the natural age of executives and carbon emission performance, while professional background and education level are negatively correlated with carbon emission performance. However, natural age is significantly related to carbon emission performance in small and medium-sized enterprises. In the regional classification of enterprises, the natural age and professional background of the core executives of high-emitting enterprises in the eastern region are negatively correlated with carbon emission performance, while the professional background of the core executives of high-emitting enterprises in the central and western regions is positively correlated with carbon emission performance. Moreover, the natural age and educational level of executives are negatively correlated with carbon emission performance. To measure the carbon emission performance of an enterprise, the study used the balanced scorecard evaluation system (CEP). Meanwhile, it innovatively classifies and sorts the sample companies based on their overall size and distribution area, and analyzes the carbon performance and executive characteristics from two perspectives. The study provides suggestions and countermeasures for companies in China, especially those in high-emission industries, to help reduce pollution.